Use of Waste from Granite Gang Saws to Manufacture Ultra-High Performance Concrete Reinforced with Steel Fibers - Fernando López Gayarre; Jesús Suárez González; Iñigo Lopez Boadella; Carlos López-Colina Pérez; Miguel Serrano López (Applied Sciences, 2021)
The purpose of this study is to analyze the feasibility of using the ultra-fine waste coming from the granite cutting waste gang saws (GCW-GS) to manufacture ultra-high performance, steel-fiber reinforced concrete (UHPFRC). These machines cut granite blocks by abrasion using a steel blade and slurry containing fine steel grit. The waste generated by gang saws (GCW-GS) contains up to 15% Fe2O3 and up to 5% CaO. This is the main difference from the waste produced by diamond saws (GCW-D). Although this waste is available in large quantities, there are very few studies focused on recycling it to manufacture any kind of concrete. In this study, the replaced material was the micronized quartz powder of natural origin used in the manufacture of UHPRFC. The properties tested include workability, density, compressive strength, elasticity modulus, flexural strength, and tensile strength. The final conclusion is that this waste can be used to manufacture UHPFRC with a better performance than that from diamond saws given that there is an improvement of their mechanical properties up to a replacement of 35%. Even for higher percentages, the mechanical properties are within values close to those of control concrete with small decreases.